The impact of UN and US economic sanctions on GDP growth - Matthias Neuenkirch; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
In this paper, we empirically assess how economic sanctions imposed by the UN and the US affect the target states' GDP growth. Our sample includes 68 countries and covers the period 1976 - 2012. We find that sanctions imposed by the UN have a statistically and economically significant influence on economic growth, but that the effect of US sanctions is less clear. On average, the imposition of UN sanctions decreases the target state's real per capita GDP growth rate by 2.3 - 3.5 percentage points (pp). Comprehensive UN economic sanctions, that is, embargoes affecting nearly all economic activity, trigger a reduction in GDP growth by more than 5 pp.
Keywords: F43; F51; F52; F53; 330; Economic growth; economic sanctions; United Nations; United States